2s(t+-7)+-6t(s+3)=

Simple and best practice solution for 2s(t+-7)+-6t(s+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2s(t+-7)+-6t(s+3)= equation:


Simplifying
2s(t + -7) + -6t(s + 3) = 0

Reorder the terms:
2s(-7 + t) + -6t(s + 3) = 0
(-7 * 2s + t * 2s) + -6t(s + 3) = 0
(-14s + 2st) + -6t(s + 3) = 0

Reorder the terms:
-14s + 2st + -6t(3 + s) = 0
-14s + 2st + (3 * -6t + s * -6t) = 0

Reorder the terms:
-14s + 2st + (-6st + -18t) = 0
-14s + 2st + (-6st + -18t) = 0

Combine like terms: 2st + -6st = -4st
-14s + -4st + -18t = 0

Solving
-14s + -4st + -18t = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '18t' to each side of the equation.
-14s + -4st + -18t + 18t = 0 + 18t

Combine like terms: -18t + 18t = 0
-14s + -4st + 0 = 0 + 18t
-14s + -4st = 0 + 18t
Remove the zero:
-14s + -4st = 18t

Combine like terms: 18t + -18t = 0
-14s + -4st + -18t = 0

Factor out the Greatest Common Factor (GCF), '-2'.
-2(7s + 2st + 9t) = 0

Ignore the factor -2.

Subproblem 1

Set the factor '(7s + 2st + 9t)' equal to zero and attempt to solve: Simplifying 7s + 2st + 9t = 0 Solving 7s + 2st + 9t = 0 Move all terms containing s to the left, all other terms to the right. Add '-9t' to each side of the equation. 7s + 2st + 9t + -9t = 0 + -9t Combine like terms: 9t + -9t = 0 7s + 2st + 0 = 0 + -9t 7s + 2st = 0 + -9t Remove the zero: 7s + 2st = -9t The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| (4x+8)(8x-4)=0 | | 3x+9=8x+3 | | 5g-2+4g+20=180 | | (7x-4)=(x+32) | | y=-7x+b | | -3(x+4)+4x=-2 | | x/3+7=2 | | 4x+14=6/5+7 | | 74-22=13Y | | 7.92y=2.2x | | .10(x)+.25(y)=12.55 | | 39.95-0.49x=75 | | 8(j-3)=4j+9j+-14 | | 125+55x=400 | | X^2+y^2+2x+4y=20 | | 3y=8x | | -3(2x-4)+8x=20 | | 15y=5x | | y^2-8y+0=0 | | 6(7-10x)+3(3-15x)=336 | | 25-4x=97 | | 10(x)+25(y)=12.55 | | 7-1.5ln*15= | | 5(y+2)-3=y-5+y | | 8C^4/11C^4 | | 3x+2x-1=69 | | (10x-9)=(4x+57) | | 7(x+7)=6(x+6) | | 8m+1=5 | | 5(3x-4)+2x-15=8x+120-3x | | 3*8*9=x | | .08x=.05x+15 |

Equations solver categories